Predicting Lifestyle and Marital Intimacy on the Tendency to Marital Infidelity in Women - moradi, zohreh; malaki, marjan; namjo, farhad (Psychology of Woman Journal, 2020)
This research was conducted to predict the tendency to marital infidelity in women: with the predictive role of lifestyles and marital intimacy. The current study was descriptive and correlational, and the statistical population of the research was women working in the offices of Karaj city in 2019; out of the statistical population, 250 women were selected and studied through available sampling. To collect data, a lifestyle questionnaire (LSQ), Bagarozzi's marital intimacy (2001), and Marami and Khademi's (2012) tendency to marital infidelity were used. After collecting and extracting data, participants' scores were analyzed using Pearson's correlation coefficient and multiple regression analysis. The results showed a significant relationship between lifestyles and marital intimacy and the tendency to marital infidelity in working women. Also, the results showed that the dimensions of lifestyles and the dimensions of marital intimacy could significantly predict the tendency of marital infidelity in working women. The findings of this research show that marital intimacy and lifestyles of married women significantly contribute to predicting the attitude towards marital infidelity.